Soil‐nitrogen, potentially mineralizable‐nitrogen, and field condition information marginally improves corn nitrogen management. (24th July 2020) - Clark, Jason D.; Fernández, Fabián G.; Veum, Kristen S.; Camberato, James J.; Carter, Paul R.; Ferguson, Richard B.; Franzen, David W.; Kaiser, Daniel E.; Kitchen, Newell R.; Laboski, Carrie A. M.; Nafziger, Emerson D.; Rosen, Carl J.; et al.
Abstract: Anaerobic potentially mineralizable nitrogen (PMN) combined with preplant nitrate test (PPNT) or pre‐sidedress nitrate test (PSNT) may improve corn ( Zea mays L.) N management. Forty‐nine corn N response studies were conducted across the U.S. Midwest to evaluate the capacity of PPNT and PSNT to predict grain yield, N uptake, and economic optimal N rate (EONR) when adjusted by soil sampling depth, soil texture, temperature, PMN, and initial NH4 –N from PMN analysis. Pre‐plant soil samples were obtained for PPNT (0‐ to 30‐, 30‐ to 60‐, 60‐ to 90‐cm depths) and PMN (0‐ to 30‐cm depth) before corn planting and N fertilization. In‐season soil samples were obtained at the V5 corn development stage for PSNT (0‐ to 30‐, 30‐ to 60‐cm depths) at 0 kg N ha −1 at‐planting rate and for PMN when 0 and 180 kg N ha −1 was applied at planting. Grain yield, N uptake, and EONR were best predicted when separating soils by texture or sites by annual growing degree‐days and including PMN and initial NH4 –N with either NO3 –N test. Using PSNT (mean R 2 = .30)‐instead of PPNT (mean R 2 = .19)‐based models normally increased predictability of corn agronomic variables by a mean of 11%. Including PMN and initial NH4 –N with PPNT or PSNT only marginally improved predictability of grain yield, N uptake, and EONR ( R 2 increase ≤ .33; mean R 2 = .35). Therefore, including PMN with PPNT or PSNT is not suggested as a tool to improve N fertilizer management in the U.S. Midwest.